2019
DOI: 10.1002/jmri.26857
|View full text |Cite
|
Sign up to set email alerts
|

Whole‐tumor histogram analysis of monoexponential and advanced diffusion‐weighted imaging for sinonasal malignant tumors: Correlations with histopathologic features

Abstract: Background: The histopathological basis of monoexponential diffusion-weighted imaging (DWI), intravoxel incoherent motion (IVIM), and diffusion kurtosis imaging (DKI) in the characterization of sinonasal malignant tumors is still unclear. Purpose: To explore the correlations of histogram metrics from monoexponential DWI, IVIM, and DKI with histopathologic features in sinonasal malignant tumors. Study Type: Retrospective. Subjects: In all, 76 patients with sinonasal malignant tumors. Field Strength/Sequence: Fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 37 publications
1
9
0
Order By: Relevance
“…The D* value reflects perfusion-sensitive information, such as microvessels density, vascular size, and vascular permeability. 37 In this study, no significant association was found between D* and the histopathological features, which agreed with the findings of Xiao et al 35 Therefore, the D* value might not accurately reflect the histopathological features of RMS.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The D* value reflects perfusion-sensitive information, such as microvessels density, vascular size, and vascular permeability. 37 In this study, no significant association was found between D* and the histopathological features, which agreed with the findings of Xiao et al 35 Therefore, the D* value might not accurately reflect the histopathological features of RMS.…”
Section: Discussionsupporting
confidence: 87%
“…Multiple linear regression analysis showed that the f value was an independent correlation factor of stroma fraction. In a study by Xiao et al 35 in sinonasal malignant tumors, the f value was significantly correlated with the cellular characteristics of the stroma fraction. This could be due to the specific tumor stroma structure and high proliferation state of cells that promoted the formation of a rich capillary network and active angiogenesis, and therefore, showed a higher f value in IVIM imaging 36 .…”
Section: Discussionmentioning
confidence: 92%
“…Some authors have discussed the theoretical basis of skewness and kurtosis and questioned the reliability and usability of those parameters 14,22 . On the other hand, several recently published studies have used these metrics (e.g., for tumor differentiation) and, upon evaluating their repeatability and correlations with clinical findings, have reported promising results 23–25 . Based on these findings, kurtosis may be regarded as a reliable biomarker with certain clinical potential if the analyzed data set is sufficiently large.…”
Section: Discussionmentioning
confidence: 99%
“…In this respect, much attention has been devoted to comparing the performance of different derived parameters with the aim of identifying the most promising diffusion model or biomarker for specific clinical purposes. For example, Xiao et al compared the predictive effect of histogram metrics calculated from monoexponential and advanced DWI in sinonasal malignant tumors [ 13 ], and Granate et al evaluated Gaussian and non-Gaussian DWI models for the differentiation of pancreatic lesions [ 14 ]. However, quantitative IVIM parameters may lack expression of the complexity of tissue microstructure, whereas the ultra-high b-value imaging of DKI may also be affected by perfusion.…”
Section: Introductionmentioning
confidence: 99%